Environmental predictors of the distribution of Franciscana dolphin (Pontoporia blainvillei) - Gomez, Jonatan José (2015)
The aim of this study was to use species distribution models to estimate the effects of environmental variables on the habitat suitability of river dolphins Pontoporia blainvillei (franciscanas) along their overall biogeographical distribution. Based on the literature, we selected six environmental variables to be included in the models; four climatic factors (surface sea temperature, salinity, turbidity and productivity) and two biotic factors (prey availability and fishing effort). We determined that the biographic range is under the following limits: temperature less than 19°C, a salinity of 36 psu and a minimal probability of the occurrence of fish C. guatucupa of 0.297. In the discussion, we postulate hypotheses on the behavioural and physiological mechanisms that cause these associations between environmental predictors and Franciscanas distribution. There was a good fit between the distribution predicted by the species distribution model and the one proposed by the experts of the International Union for Conservation of Nature; however, our analysis failed to highlight the fundamental role of bycatch as the main threat to this dolphin species.